Low-cost quadrotor hardware design with PID control system as flight controller - Adnan Rafi Al Tahtawi; Maulana Yusuf (Universitas Ahmad Dahlan, 2019)
In designing an Unmanned Aerial Vehicle (UAV), such as quadrotor, sometimes an engineer should consider the required cost that is relatively expensive. As we know, quadrotor is one of robots that very usefull and has several advantages for human needs such as disaster area monitoring, air quality monitoring, area mapping, aerial photography, and surveillance. Thus, designing a rapid quadrotor with low-cost components and simple control system needs to be considered here. This paper presents design and implementation of a quadrotor using relatively low-cost components with Proportional Integral Derivative (PID) control system as its controller. The components used consist of microcontroller, Inertial Measurement Unit (IMU) sensor, Brushless Direct Current (BLDC) motor, Electronic Speed Control (ESC), remote control unit, battery, and frame. These components can be easily found in the electronic markets, especially in Indonesia. As an addition, this paper also describes PID control system as flight controller. A simple economic analysis is presented to clarify the cost in designing this quadrotor. Based on experimental testing result, the quadrotor able to fly stably with PID controller although there still overshoot at the attitude responses.